An information system to manage the rollout of the antiretroviral treatment programme in the Free State - J.E. Kotzé; T. McDonald (AOSIS, 2010)
The Acquired Immune Deficiency Syndrome epidemic, caused by the Human Immunodeficiency Virus, is a global crisis which threatens development gains, economies, and societies. Within sub-Saharan Africa, where the epidemic began the earliest and the HIV prevalence is the highest, African countries have death rates not seen before. In South Africa the epidemic has a devastating impact which creates profound suffering on individuals and their families, and the impact on the socio-economic level is of great concern. The eradication of HIV/AIDS represents one of humanity's greatest challenges, which requires co-operation and comprehensive collaboration between many different role players. In this endeavour clinical information plays a major role. To combat the effect of the disease, the Free State Department of Health started with the provisioning of antiretroviral therapy in the public health sector. The objective of this paper was to address the challenges they faced in order to develop and implement an information system to manage the rollout of antiretroviral treatment effectively. They started with a paper-based system to collect vital information. It was followed by a palm computer project that was initiated to electronically capture the data collected by the paper-based system. This system was then replaced by a comprehensive Hospital and Clinic Information System which was acquired and customised for the antiretroviral data collection process. Research partners developed a standalone antiretroviral data warehouse for collecting information associated with the monitoring and evaluation of the Free State antiretroviral and HIV/ AIDS treatment programme. The data warehouse successfully produced several management information reports to the antiretroviral management team. A need was identified to design a comprehensive antiretroviral data warehouse that will integrate data from several operational sources which are all associated with HIV/AIDS.